2013
DOI: 10.1017/s1751731111002394
|View full text |Cite
|
Sign up to set email alerts
|

Managing variations in dairy cow nutrient supply under grazing

Abstract: Grazed pasture, which is the cheapest source of nutrients for dairy cows, should form the basis of profitable and low-input animal production systems. Management of high-producing dairy cows at pasture is thus a major challenge in most countries. The objective of the present paper is to review the factors that can affect nutrient supply for grazing dairy cows in order to point out areas with scope for improvement on managing variations in nutrient supply to achieve high animal performance while maintaining eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 52 publications
5
77
1
Order By: Relevance
“…In our study, higher pasture nutritional values were observed compared with those reported by McEvoy et al (2008), Bargo et al (2002) and Pérez-Prieto et al (2011), promoting higher pasture intake and lower grass to concentrate substitution rate. The negative MR observed in May presumed a low substitution rate and could be explained by the high WSC content of spring pasture promoting increase in pasture intake and in MY, which is in accordance with other authors (Peyraud and Delagarde, 2013;John et al, 2016).…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, higher pasture nutritional values were observed compared with those reported by McEvoy et al (2008), Bargo et al (2002) and Pérez-Prieto et al (2011), promoting higher pasture intake and lower grass to concentrate substitution rate. The negative MR observed in May presumed a low substitution rate and could be explained by the high WSC content of spring pasture promoting increase in pasture intake and in MY, which is in accordance with other authors (Peyraud and Delagarde, 2013;John et al, 2016).…”
Section: Impact On Voluntary Cow Trafficsupporting
confidence: 91%
“…Following the literature (Dufrasne et al, 1996;Reis and Combs, 2000;Bargo et al, 2002;Kennedy et al, 2003;McEvoy et al, 2008;Auldist et al, 2013), several factors influence the effect of concentrates supplementation on average milk yield and composition -for example, pasture availability and quality, stage of lactation and genetic merit. At high pasture allowance, pasture quality influences pasture intake: Peyraud and Delagarde (2013) reported that pasture intake could vary from 18.9 kg DM/cow per day for excellent pasture quality to 15.5 kg DM/cow per day in very poor pasture quality. In our study, higher pasture nutritional values were observed compared with those reported by McEvoy et al (2008), Bargo et al (2002) and Pérez-Prieto et al (2011), promoting higher pasture intake and lower grass to concentrate substitution rate.…”
Section: Impact On Voluntary Cow Trafficmentioning
confidence: 99%
See 3 more Smart Citations